Prediction of Thermal Conductivity of a Rock Wool Board by Computer X-Ray Tomography Technique Scanning and Random Generation-Growth Model - Xiaoguang Li; Rui Zhang; Diya Zhang; Xin Fan; Meiqi Guo; Jinyi Qin (Advances in Materials Science and Engineering)
Thermal conductivity of rock wool boards was investigated in this study. Although distribution of fibers in a realistic rock wool board is unclear, it can be simulated by computer X-ray tomography technique (CT) followed by rearrangement through the random generation-growth (RGG) model. An ideal CT-RGG structure model of rock wool boards (CT-random generation-growth model) was established by simplifying material properties based on the mesostructure parameters of the RGG model. Thermal conductivity of rock wool boards with different apparent densities and fiber diameters was studied, and the CT-RGG model was analyzed by explicit jump (EJ) diffusion equations solved by the fast Fourier transform method. We found that thermal conductivity of a single rock wool fiber can be successfully determined. Simulation and measurement results show that thermal conductivity increases consistently with the increase of apparent density and fiber diameter, particularly when the apparent density of rock wool board is greater than 140 kg m−3. Compared with the existing theoretical models, the proposed method does not depend on the empirical parameters; therefore, it is useful in designing and optimizing the thermal conductivity of rock wool boards.